Damage Concentration Effect of Multistory Buckling-Restrained Braced Frames - Hanqin Wang; Yulong Feng; Jing Wu; Qing Jiang; Xun Chong (Advances in Civil Engineering)
Due to the low postyield stiffness of buckling-restrained braces (BRBs), multistory buckling-restrained braced frames (BRBFs) subjected to earthquakes are prone to lateral deformations and damage concentrations at certain stories, which is deemed a damage concentration effect (DCE). A series of nonlinear pushover analyses and response history analyses are conducted to investigate the key factors affecting the DCE of BRBFs. Two comparisons of the DCE are performed for different types of structures and different beam-to-column connections in the main frame (MF). These comparisons show that BRBFs equipped with BRBs as the main earthquake resistance system have a more serious DCE than the traditional moment-resisting frame or conventional braced frame and that the MF stiffness significantly affects the structural residual displacement and DCE. Then, parametric analyses are performed to investigate the influence of two stiffness distribution parameters (in the horizontal and vertical directions) on the DCE of a 6-story BRBF dual system designed according to the Chinese seismic code. The results show that increasing the MF stiffness and avoiding abrupt changes in the BRB stiffness between stories can effectively mitigate the DCE of BRBFs. Finally, the correlations between various damage performance indices are analyzed. A low statistical correlation between the peak and residual drift responses can be observed in BRBFs. Therefore, it is recommended that the DCE be considered in BRBF design.